Manajemen Konflik dan Resolusi Konflik: Sebuah Pendekatan Terhadap Perdamaian - Penny Kurnia Putri (Cenderawasih University, 2022)
Although much literature has examined conflict management and conflict resolution, there have not yet been systematic studies that focus on their discrepancies. This article aims to explore the difference between conflict management and conflict resolution in the context of international relations. The discussion includes the theoretical and practical aspects of both approaches to peace based on a literature review of primary texts in Security and Peace Studies. This study adopts a qualitative descriptive method to shed light on the difference between the two approaches. In reference to the concept of negative and positive peace, theoretically, conflict management is engaged in negative peace, and conflict resolution in positive peace. Conflict management has the output to open room for peace processes such as negotiations, and conflict resolution to create peace agreements. Both approaches contribute significantly as keys to the transition towards peace through peace operations and supporting mechanisms to bring the finest negotiations. KEYWORDSConflict Management; Conflict Resolution; Negotiation; Peace